MCU complex: Exploring emerging targets and mechanisms of mitochondrial physiology and pathology - Jin Wang; Jinyong Jiang; Haoliang Hu; Linxi Chen (Journal of Advanced Research)
Background: Globally, the onset and progression of multiple human diseases are associated with mitochondrial dysfunction and dysregulation of Ca2+ uptake dynamics mediated by the mitochondrial calcium uniporter (MCU) complex, which plays a key role in mitochondrial dysfunction. Despite relevant studies, the underlying pathophysiological mechanisms have not yet been fully elucidated. Aim of review: This article provides an in-depth analysis of the current research status of the MCU complex, focusing on its molecular composition, regulatory mechanisms, and association with diseases. In addition, we conducted an in-depth analysis of the regulatory effects of agonists, inhibitors, and traditional Chinese medicine (TCM) monomers on the MCU complex and their application prospects in disease treatment. From the perspective of medicinal chemistry, we conducted an in-depth analysis of the structure–activity relationship between these small molecules and MCU and deduced potential pharmacophores and binding pockets. Simultaneously, key structural domains of the MCU complex in Homo sapiens were identified. We also studied the functional expression of the MCU complex in Drosophila, Zebrafish, and Caenorhabditis elegans. These analyses provide a basis for exploring potential treatment strategies targeting the MCU complex and provide strong support for the development of future precision medicine and treatments. Key scientific concepts of review: The MCU complex exhibits varying behavior across different tissues and plays various roles in metabolic functions. It consists of six MCU subunits, an essential MCU regulator (EMRE), and solute carrier 25A23 (SLC25A23). They regulate processes, such as mitochondrial Ca2+ (mCa2+) uptake, mitochondrial adenosine triphosphate (ATP) production, calcium dynamics, oxidative stress (OS), and cell death. Regulation makes it a potential target for treating diseases, especially cardiovascular diseases, neurodegenerative diseases, inflammatory diseases, metabolic diseases, and tumors.